Determinants of symptom variation of Pepper yellow leaf curl Indonesia virus in bell pepper and its spread by Bemisia tabaci - DEWA GEDE WIRYANGGA SELANGGA; LISTIHANI LISTIHANI; I GEDE RAI MAYA TEMAJA; GUSTI NGURAH ALIT SUSANTA WIRYA; I PUTU SUDIARTA; KETUT AYU YULIADHI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Selangga DGW, Listihani L, Temaja IGRM, Wirya GNAS, Sudiarta IP, Yuliadhi KA. 2023. Determinants of symptom variation of Pepper yellow leaf curl Indonesia virus in bell pepper and its spread by Bemisia tabaci. Biodiversitas 24: 869-877. Pepper yellow leaf curl Indonesia virus (PYLCIV) is an important virus that infects chili pepper in Indonesia. PYLCIV has been reported in several regions in Indonesia on several host plants, such as chili pepper, tomato, sweet potato, and ornamental plants. PYLCIV infection has never been reported in bell pepper plants, in 2021 we found yellow mosaic symptoms on bell pepper leaves so this research aimed to conduct molecular characterization on the virus causing yellow leaf curl disease in bell pepper and its relationship to distribution and symptoms variations in the field. The research method includes symptom observation, disease incidence, the population of Bemisia tabaci in the field, and molecular detection via PCR on PYLCIV obtained from bell pepper leaf and on B. tabaci imago. PYLCIV infection in a bell pepper is differentiated into five types of symptoms: mottle, leaf curl and malformation, yellowing, green mosaic, and yellow mosaic. The symptoms type often found in bell pepper plants are yellow mosaic and leaf curl and malformation, with the incidence rates being 19.5% and 21.5%, respectively. The high whitefly population in both symptoms type caused the high incidence rate. Moreover, via PCR, whiteflies on bell pepper with those five symptom types were positive for Begomovirus (B. tabaci viruliferous). Bell pepper positive for PYLCIV appeared to have long fruit ripening periods with small sizes, elongated shaped, and abnormal. While healthy bell pepper showed rapid ripening and large and plentiful fruits. The five symptom types of PYLCIV from bell pepper showed the highest nucleotide homology with PYLCIV isolates from Selulung Village, Kintamani Sub-district, Bangli District, Bali Province, Indonesia, obtained from chili pepper with a homology of 99.7-99.8%. The phylogenetic tree showed that the five symptom types PYLCIV in bell pepper formed a group with PYLCIV isolate from Selulung obtained from chili pepper. This research is the first report of PYLCIV infection on bell pepper in Indonesia.